Exploration and visualization of race biking performance - Byshko, R. (Sportinformatik trifft Sporttechnologie. 8. Symposium der dvs-Sektion Sportinformatik in Kooperation mit der Deutschen Interdisziplinären Vereinigung für Sporttechnologie vom 15.-17. September in Darmstadt, 2011)
We develop methods and tools for visual analytics to help analysing performance parameters in race biking. The work described in this paper is done as a part of the Powerbike (Dahmen et al., 2009) project at the University of Konstanz, the goal of which is to provide methods to model, analyze, visualize, and improve the performance of athletes during the training and in competition in cycling. In a laboratory, the measurements combined from a series of devices, including conventional bike computers, GPS-recorders, and power meters are processed. The data is recorded by different devices and synchronized and fused beforehand, yielding a collection of time series (with sampling rate of 1Hz) for the various performance parameters. Paper addresses the problem to present all this data on one screen for the trainer or cyclist so they can quickly grasp the main trends in it to be able to make decisions about further training.